PENGENDALIAN PENCAHAYAAN ALAMI BTP INNOVATION GALLERY MELALUI INTERIOR SHADING SYSTEM - Abdulhadi, Reza Hambali Wilman; Hapsoro, Agustinus Nur Arief; Perdana, Aditya Bayu; Nugroho, Ardianto (Narada : Jurnal Desain dan Seni, 2024)
In the design of a space, daylighting related to space lighting standards, as well as the visual comfort of users are important to fulfill. In terms of lighting control, natural lighting is difficult to control because it always changes based on the weather, time of day, month, building orientation and inclination angle. Architecture, fullfill visual comfort through natural light and it is usually done through building orientation, use of types of openings, glass, landscape elements in relation to control the amount of light entering the room. Meanwhile, in the realm of interior design, the strategy for meeting the level of illuminance is usually carried out through arranging the layout and elements behind the windows such as curtains, vitrasse and roller blinds which are integrated with an artificial lighting system. Another phenomenon encountered is that many buildings use glass facades, thus implementing sun shading on the outside of the building, become a problem. It is necessary to think about other strategies for this problem. This is what researchers suspect is happening in the BTP Innovation Gallery, where the entire building facade uses glass. For this reason, it is necessary to develop interior elements to overcome building problems, especially those that use glass facades on almost the entire building. To provide development of existing technology in interior space, the research carried out was in the form of developing a strategy for controlling indoor light (interior shading system) statically through simulation tests using dialux software. The research method was carried out using quantitative methods by first analyzing the illumination that occurs inside the building. In the next stage, experiments were carried out with different shading system forms and with different opening angles. From the research results, it was concluded that the interior shading system that approaches the uniformity of illuminance ratio value is the interior shading system with a vertical shape of 45 degrees, although the resulting value cannot be said to be perfect because the value is still below the required standard.